2017
DOI: 10.2344/anpr-64-02-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Articaine and Lidocaine for Buccal Infiltration After Inferior Alveolar Nerve Block For Intraoperative Pain Control During Impacted Mandibular Third Molar Surgery

Abstract: In order to compare the efficacy of lidocaine and articaine for pain control during third molar surgery, 160 patients presenting bilateral asymptomatic impacted mandibular third molars were selected. They received 1.8 mL of 2% lidocaine with epinephrine 1:100,000 during inferior alveolar nerve block. In group 1 (n = 80), an infiltrative injection of 0.9 mL of 2% lidocaine with epinephrine 1:100,000 was performed in buccal-distal mucosa of the third molar. Group 2 (n = 80) received 0.9 mL of 4% articaine with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…Pain measurement is always difficult to establish, because its perception and intensity are multifactorial, however the direct self-report is the most common in clinical practices [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pain measurement is always difficult to establish, because its perception and intensity are multifactorial, however the direct self-report is the most common in clinical practices [7].…”
Section: Discussionmentioning
confidence: 99%
“…Resin infiltration may be more effective, especially in areas with shallow defects. 33,[40][41][42][43] However, defects involving the entire width of enamel may require conventional approaches, such as composite resin restorations, particularly if the carious process has involved one or more surfaces with using self-etching adhesive. Full coverage restorations, such as stainless-steel crowns are good options for teeth with severely damaged surfaces.…”
Section: Restorations or Extractionsmentioning
confidence: 99%
“…[53][54][55][56] Extraction may be the treatment of choice for non-restorable teeth or those with poor prognoses, but in very young children, occlusal guidance must be utilized to ensure that the second permanent molars move in position of the first molar. 33,40,[53][54][55][56][57] Many factors must be considered, especially in cases involving the mandibular arch. The optimal timing for extractions is evidently between the ages of 8 and 10 years.…”
Section: Restorations or Extractionsmentioning
confidence: 99%
“…The patients received the necessary information regarding the NRS in terms of pain intensity level ranging from 1 to 10, i.e. no pain (0), mild pain (1-3), moderate pain (4-6), and severe pain (7)(8)(9)(10). This was done before the initiation of the surgical procedure to help the patient score his or her pain reliably.…”
Section: Pain Assessmentmentioning
confidence: 99%
“…Moreover, Silva-Junior, Almeida, and Groppo reported on using the infiltration technique after inferior alveolar nerve injections to release intraoperative pain. They concluded that buccal infiltration after inferior alveolar injections enhances the effectiveness of inferior alveolar nerve injections that show a 10-26.3% failure rate [8].…”
Section: Introductionmentioning
confidence: 99%